Virtual Reality-based Simulation of Age-related Declines - Zavlanou, Christina (My University, 2022)
Albeit utterly important in an aging world, understanding and addressing elderly people’s needs is no easy task, as aging relates to a complex mechanism of a natural process affecting the quality of elderly life in different ways. For this, harnessing Virtual Reality, the present research proposes a perspective-taking approach that simulates common age-related declines to provide a first-hand experience of the latter and their associated challenges. At an initial stage, the research focused on the development and the effectiveness assessment of a prototype simulation in different cases, addressing mainly the need for contemporary technological tools to facilitate elderly-friendly design. The results demonstrated its potential to induce the sense of being older and identify design weaknesses from the perspective of elderly impaired adults. The proposed simulation even outperformed other methods used for this purpose, on several measures. At a second stage, focusing on vision, a novel technical approach was implemented to generate procedural declines, giving the possibility to experience their different nuances in virtual environments. To validate the soundness of the simulation vis-à-vis its intended purpose, three tests were conducted and the results obtained were examined with regards to actual data, to assess whether the simulated effects induce similar impairments to the actual declines. Taken together, the results demonstrate that the proposed approach can be leveraged as a supportive tool in the design process, and in a broader context for understanding physical problems related to aging and how these affect the life of many elderly people.
Keywords: Vittual Reality; Simulating; Aging Effects